SOCIAL CONSTRUCTION OF RESPONSIBILITY IN SIRI POLYGAMY IN MADURA - Adiyono; Rudi Hermawan; Agustina Kumala Dewi Sholihah; Hawa Gazani; Ach. Mus’if (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2026)
This study examined siri polygamy (unregistered polygamy) in Madurese society, focusing on second and third wives and community leaders. It investigated the husband's